(PriCotton Brotherz Group) Printing and clothing business / Aniq Izdihar Khuzairi Roslam ... [et al.] - Aniq Izdihar Khuzairi, Roslam; Muhammad Danish Danial, Khairudin Jaffry; Muhamad Syahir Aqil, Norizal; Muhamad Faiz, Muhamad Izhar; Mohamad Luqman Hakim, Mohamad Yazid; Mohd Noor Shazwan, Shabudin (2019)
The busniness we take is fabric business, on this subject we are given a task to do an interview from a company that we altogether agree. We choose a Dyana Cotton that are managed by Mohd Nasri Bin Ishak. This business established from 2012 until now. His business started from the bottom and only uses Rm 5000 to start his business. From the beginning he only open one stall at Jalan Tar, Kuala Lumpur. In this interview we gained a lot of information for our study. We learned that there is a problem that this company are facing and we come out with the most suitable solution to that problem. The biggest problem they are fadng is having a competitor for example having Jakel and Gulatis as their competitor. Here are three business that we would like to propose in order to overcome these problems. The goal we think for this idea can do with shop fabric is sell more creative and exclusive design and sell men's clothe but still with theme the fabric cotton. Why we choose this idea this is because we want to customer and people can have a more choice and get a more product we can do. So this can give effect at we business to be a great business. Second is post service and online business this is because we can make the business more reachable to other areas. So this can give a positive effect at buy and we business because more people can know what there want at we shop via a online and can give a post service at customer after there by any product at we shop. Third idea is open a cafe and combine with shop after that give a free Wi-Fi to customer. The reason is we want attraction and comfort for customer is very important to we give at customer. The cafe can be place to customer or any people want to rest or dinning at my shop and the same time can see product we sale. This idea we give and we think suitable for we business and we think is a new idea in the normal business like another business. In addition, it can be a great business. The choice idea we give we have a one choose is sell more creative and exclusive design. This is because we think want to create a new design and suitable this is good idea can give a customer choice and we design follow the era or trending fashion. The design we create a interesting design better more like before design at fabric and create a more product use a fabric cotton not just a t-shirt but we want to create a new product use a fabric like hand bag and cover wallet. This reference we is style batik product there use the batik fabric but the product different like another thinking. There use the batik create a t-shirt for men and cover sandal.